Speech on the limits of obedience: enunciates that emphasize or disguise conflicts between Mandetta and Bolsonaro during the crisis of the coronavirus in Brazil - Fabbri Jr, Duílio; Ormaneze, Fabiano (Faculdade de Ciências e Letras - Unesp - Araraquara., 2020)
This paper analyzes declarations by the Brazilian Minister of Health, Luiz Henrique Mandetta, during the pandemic period, caused by the new coronavirus, in March 2020. Through the theoretical-methodological reference of the French Discourse Analysis, the meanings produced through speeches are compared in two press conferences, before and after President Jair Bolsonaro’s speech, minimizing the effects of the disease and reacting negatively to the containment measures adopted by Brazilian states, based on the guidelines of the Ministry of Health, endorsed by the World Health Organization (WHO) and following measures implemented by other countries. The different political and scientific points of view ended up with the minister being fired by the President. Thus, we reflect on the meanings of democracy, authoritarianism, trust and obedience in the clashes of power relations. The discursive analysis of the speeches of the Minister of Health brings the (un)visible presence on the government’s stance regarding the pandemic, supporting elements of authoritarianism, causing disinformation among Brazilians.